2001
DOI: 10.2527/2001.7911
|View full text |Cite
|
Sign up to set email alerts
|

Calf removal improves conception rates to the Ovsynch and CO-Synch protocols.

Abstract: Beef cows (n = 473) from two locations were stratified by breed, postpartum interval, age, and AI sire and were randomly allotted to one of four treatments for synchronization of ovulation. Ovulation synchronization protocols included the Ovsynch protocol with (n = 114) or without (n = 123) 48-h calf removal from d 7 to 9 (d 0 = 1st GnRH injection) or the CO-Synch protocol with (n = 119) or without (n = 117) 48-h calf removal from d 7 to 9. The Ovsynch protocol included administration of GnRH (100 microg; i.m.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
3
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 13 publications
(21 reference statements)
3
41
3
13
Order By: Relevance
“…The interval to first postpartum ovulation was reduced by an average of 23 days (P < 0.02) if cows suckled calves only once per day beginning at 30 days postpartum (Stagg et al, 1998). Effects of calf removal were most favorable when associated with timed inseminations (Kiser et al, 1980;Geary et al, 2001b) and if cows were in sub-optimal body condition (Kiser et al, 1980), but were less reliably observed in cows mated at estrus (Geary et al, 2001a). In sheep, reducing suckling intensity by separating spring-lambing ewes from their lambs during the daylight hours had no obvious positive effect on spring fertility (Whiteman et al, 1972), but that study did not include a control group.…”
Section: Discussionmentioning
confidence: 88%
“…The interval to first postpartum ovulation was reduced by an average of 23 days (P < 0.02) if cows suckled calves only once per day beginning at 30 days postpartum (Stagg et al, 1998). Effects of calf removal were most favorable when associated with timed inseminations (Kiser et al, 1980;Geary et al, 2001b) and if cows were in sub-optimal body condition (Kiser et al, 1980), but were less reliably observed in cows mated at estrus (Geary et al, 2001a). In sheep, reducing suckling intensity by separating spring-lambing ewes from their lambs during the daylight hours had no obvious positive effect on spring fertility (Whiteman et al, 1972), but that study did not include a control group.…”
Section: Discussionmentioning
confidence: 88%
“…De forma similar, foi relatado que o efeito da RTB pode variar conforme a raça (Sanz et al, 2003) ou a idade das vacas (Geary et al, 2001;Santos & Santos, 2003).…”
Section: Resultsunclassified
“…Foram utilizadas vacas da raça Nelore e mestiças (Nelore × Red Angus) com 60 a 90 dias pós-parto e escore de condição corporal de 2,5 a 3,5 (1 = muito magra a 5 = muito gorda), segundo Lowman et al (1976). Os animais foram manejados extensivamente em pastagens de Brachiaria brizantha e receberam suplementação mineral ad libitum.…”
Section: Methodsunclassified
“…The treatment protocol currently used in dairy cattle has been called Ovsynch (Pursley et al, 1995) in which GnRH is given 56 h after PGF and cows are inseminated 16 h later (Brusveen et al, 2008). CO-Synch protocols are more commonly used in beef cattle because cows are FTAI at the time of the second GnRH (Geary et al, 2001). Recent studies have shown that the first GnRH resulted in ovulation in 44% to 54% of dairy cows (Bello et al, 2006;Colazo et al, 2009), 56% of beef heifers (Martinez et al, 1999) and 60% of beef cows (Small et al, 2009), and the emergence of a new follicular wave was synchronized only when treatment caused ovulation (Martinez et al, 1999).…”
Section: Ovulation Synchronization Treatments For Ftai In Beef Cattlementioning
confidence: 99%
“…GnRH-based protocols have been used extensively for FTAI in dairy (Pursley et al, 1995) and beef cattle (Geary et al, 2001). The treatment consists of the administration of GnRH to induce LH release and ovulation of the dominant follicle, with emergence of a new follicular wave~1.5 to 2 days later.…”
Section: Ovulation Synchronization Treatments For Ftai In Beef Cattlementioning
confidence: 99%